1991
DOI: 10.1093/jnci/83.15.1077
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Doxorubicin, Bisantrene, and Miltoxantrone in Advanced Breast Cancer: A Southwest Oncology Group Study

Abstract: Four hundred eleven women with metastatic breast cancer were randomly assigned to receive either 60 mg/m2 doxorubicin (130 patients), 320 mg/m2 bisantrene (146 patients), or 14 mg/m2 mitoxantrone (135 patients). The doses were given intravenously every 3 weeks with a cross-over design to determine their relative efficacy and toxicity. To be eligible, patients must have had one previous chemotherapy regimen, and patients who were estrogen receptor positive must have failed endocrine therapy. There were 365 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The overall response rate reported here is also comparable to those obtained from other agents, including conventional doxorubicin, epirubicin, cyclophosphamide, etoposide, and docetaxel, used singly in the second-line treatment of metastatic breast cancer [16][17][18][19][20][21][22]. The overall response rates of these agents range from 26 to 58%, with myelosuppression as the main toxicity [16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The overall response rate reported here is also comparable to those obtained from other agents, including conventional doxorubicin, epirubicin, cyclophosphamide, etoposide, and docetaxel, used singly in the second-line treatment of metastatic breast cancer [16][17][18][19][20][21][22]. The overall response rates of these agents range from 26 to 58%, with myelosuppression as the main toxicity [16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 69%
“…The overall response rates of these agents range from 26 to 58%, with myelosuppression as the main toxicity [16][17][18][19][20][21][22]. The toxicity profile of PLD reported in this study is distinctly different from these agents, including conventional doxorubicin and epirubicin.…”
Section: Discussionmentioning
confidence: 96%
“…Other doxorubicin analogs, idarubicin and mitoxantrone, although they may reduce cardiac injury, do not completely eliminate the risk of cardiotoxicity [43,48]. Studies with use of these different analogs have so far been done only in adults with breast cancer [47,48].…”
Section: Preventing Cardiotoxicitymentioning
confidence: 99%
“…Studies with use of these different analogs have so far been done only in adults with breast cancer [47,48]. To our knowledge, no studies have been conducted in adolescents that might justify the use of analogs in this group.…”
Section: Preventing Cardiotoxicitymentioning
confidence: 99%
“…As no qualitative differences in mecha nism of action have been demonstrated between EPI and doxorubicin, cross-resistance is expected. Experiments in vitro and in vivo have confirmed the existence of com plete cross-resistance between these two drugs [18], Al though there are no substantial data available concerning cross-resistance between EPI and tetrahydropyranyldoxorubicin, there is some indication that cross-resis tance seems to be incomplete in the treatment of breast cancer [19], A lack of complete cross-resistance between EPI and mitoxantrone has been noted in preclinical [20] and clinical studies [21], Nevertheless, cross-resistance was reported to be marked and only occasional crossover response was demonstrated [22], However, it is very hard to say whether the effect of the investigated regimen in pretreated patients was mainly based either on the modulation of FU by HDFA or on the lack of absolute cross-resistance to the anthracycline ana logues applied with the investigated patients. The median duration of response of 6 months appears to be satisfacto ry, especially considering that the median time under treatment was 3.2 months only.…”
Section: Discussionmentioning
confidence: 99%